2014
DOI: 10.1016/j.eurpsy.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Therapists’ professional and personal characteristics as predictors of outcome in long-term psychodynamic psychotherapy and psychoanalysis

Abstract: Results challenge the benefit of a classically "neutral" psychoanalyst in PA. They also indicate closer examinations of therapy processes within and between the two treatments, which may benefit training and supervision of therapists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 54 publications
0
24
1
1
Order By: Relevance
“…The results showed that in short‐term psychodynamic treatment, clinicians with interpersonally engaged and extroverted personalities produced faster symptom reduction, whereas patients in long‐term therapies benefited more from less intrusive therapists (Heinonen et al, ). In a 5‐year follow‐up, the same authors found that therapists who experienced themselves as less cold or detached, as well as more assertive, tended to achieve greater patients' symptom reduction (Heinonen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that in short‐term psychodynamic treatment, clinicians with interpersonally engaged and extroverted personalities produced faster symptom reduction, whereas patients in long‐term therapies benefited more from less intrusive therapists (Heinonen et al, ). In a 5‐year follow‐up, the same authors found that therapists who experienced themselves as less cold or detached, as well as more assertive, tended to achieve greater patients' symptom reduction (Heinonen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (6.67%; Berghout & Zevalkink, ; Frank, Gunderson, & Gomes‐Schwartz, ) were clinical trials and did not report treatment duration. Two studies (6.67%; Heinonen, Knekt, Jääskeläinen, & Lindfors, ; Heinonen, Lindfors, Laaksonen, & Knekt, ) used a quasi‐experimental design with a 3‐ and 5‐year follow‐up from the start of treatment, respectively. In these studies, the average treatment duration ranged from 20 sessions to 3 years (Heinonen et al, ) and from 31.3 to 56.3 months (Heinonen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible factor is the therapist's own personality. Research on psychodynamic therapists has found that personality style can affect the outcome of psychotherapy (Heinonen, Knekt, Jääskeläinen, & Lindfors, 2014;Heinonen, Lindfors, Laaksonen, & Knekt, 2012). For example, therapists who treated mood and anxiety disorders produced faster symptom reduction in short-term therapy if they were more extroverted, whereas more neutral and cautious therapists elicited better and longerlasting results in long-term therapy.…”
Section: Disordersmentioning
confidence: 99%
“…Psychologists’ confidence appeared to promote therapeutic buy‐in in the current study. Therapist confidence has been shown to predict positive client outcomes in short‐term, but not long‐term, therapy in the general population (Heinonen, Lindfors, Laaksonen, & Knekt, ). It has also been shown to enhance therapy effectiveness, client progress (Clemence, Hilsenroth, Ackerman, Strassle, & Handler, ), the therapeutic alliance and the ability to work through ruptures (Ackerman & Hilsenroth, ).…”
Section: Discussionmentioning
confidence: 99%